HUBUNGAN PENGETAHUAN KESEHATAN RAMBUT DENGAN PERILAKU PERAWATAN RAMBUT PASCA-PEWARNAAN RAMBUT (Studi Kasus Remaja Wanita Kampung Bojong Desa Pamagersari Kabupaten Bogor) - Neneng puziaawati, Ine (Universitas Negeri Jakarta, 2021)
This research is based on the differences in the behavior of adolescent women in caring for post-coloring hair and the level of knowledge of hair health in adolescent women in Kampung Bojong. To answer the extent of the relationship between knowledge of hair health and post-coloring behavior in adolescent women in Bojong Village, Pamagersari Village, Bogor Regency, a correlational approach was used quantitative research methods. Data were collected using a questionnaire that was distributed directly to female respondents who did hair coloring in Bojong Village, Pamagersari Village. The results of calculations with product moment correlation obtained rcount (rxy) = 0.637 so that > ​​0.5 so that there is a positive relationship between variable X and variable Y. From the calculation of the simple regression correlation equation the correlation between the two variables is Y = 94.599 + 0.8933X. Hypothesis with t-test, obtained tcount = 4.373 while ttable at significance level of 0.05 with dk (n-2) = (30-2) = 28 of 2.048. So tcount > ttable because 4.373 > 2.048. The conclusion is that there is a significant relationship between variable X and variable Y. KD calculations show that knowledge of hair health in adolescent women in Bojong Village, Pamagersari Village has an influence on post-hair coloring treatment behavior of 40.64%, while 59.36% is determined by other factors not calculated on this research. Knowledge of hair health in adolescent women in Bojong Village, Pamagersari Village, contributes in the form of a positive relationship to the behavior of post-coloring hair care, so that increased knowledge of hair health is very supportive of caring for post-coloring hair.